Manuel Querino: entre letras e lutas - Bahia: 1851 – 1923 - Leal, Maria das Graças de Andrade (2004)
Some aspects of the life of Manoel Querino (1851-1923) are disclosed in this biographical study, filling existent gaps on the artist, politician, professor and intellectual. His works produced between 1903 and 1922 are considered to be autobiographical and are the main path to understanding and capturing his essence from within the entanglement of his text and the context in which he lived, as an acknowledgment of someone who lived and witnessed deceptions and victories at the dawn of the Republic.He created a new way of telling history, bringing into focus social subjects who existed in a social, political and cultural penumbra and with him shared prejudice, discrimination and rejection as a consequence of social class and race. An Afro-Brazilian, born in the city of Santo Amaro da Purificação, in the state of Bahia(28 July, 1851), he lived with passion through the significant events of Brazilian histor, especially the history of Bahia, that marked the final days of the Monarchy and first days of the Republic. Given the complexity of his life, he was a singular individual and therefore a preferred subject of many biographers. It is a challenge to give him historical voice and significance while researching his involvement in social processes, both as political militant and intellectual. In pursuing justice, liberty, equality and democracy, he was committed to the causes of the people and of the working class. He raised two issues: the place the people and the workers should occupy in the Republic and the position of the Negroes in post-abolition Brazilian society. He was a militant loyal to the cause of the oppressed. From his worker upbringin, Querino made his way into partisan politics while developing his talents as an artist, having majored in art and starting his studies of architecture. During Monarchy, he was a working class militant having created the Bahian League of Workers. At the advent of the Republic he was one of the founders of the Labor Party, being elected Town Counselor for two terms (1891-1892 and 1897-1899). After resigning from politics, he started one more militancy, committing himself to teaching and knowledge. Due to the work he produced, Querino gained the respect of Bahian society while maintaining his prestige among intellectuals and blue collar workers